Dimensions of Multicultural Education for Equal Rights - Rohmat (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Opening the horizons of teachers becomes urgent in reading diversity as a necessity in the educational environment. The purpose of this study is to reformulate the meaning of education that seats students as human beings who continue to grow, and abandon violence in the world of education. Madrasa is homogeny religious, so the pattern of diversity in question is cognitive, physical and socio-cultural-economic. This research was carried out by ethnographic method with the locus of MTs throughout Cilacap Regency. The results showed: 1) The reading of diversity is interpreted in the historical sense of diversity in the Bhineka Tunggal Ika; 2) Madrasa as the cultivation of diversity values is carried out by changing the curriculum, strategies, learning models and methods, and Teachers' views on diversity; 3) Praxis for the implementation of multicultural education in madrasas is carried out by: integrative learning plans based on diversity backgrounds; Plural Classroom Management and Diversity Learning Strategies; Ethnic Studies and Social Communication Interactions and Interpersonal Relationships; Madrasa as a Medium for Maintaining Tradition in the midst of Modernity.